Neonatal Late-Onset Sepsis Following Peripherally Inserted Central Catheter Removal: Association With Antibiotic Use and Adverse Line Events. Issue 2 (March 2015) - Hoffman, Michelle A.; Snowden, Jessica N.; Simonsen, Kari A.; Nenninger, Tabitha M.; Lyden, Elizabeth R.; Anderson-Berry, Ann L.
Abstract : The objective of the study was to evaluate incidence of and risk factors for sepsis following peripherally inserted central catheter (PICC) removal. The retrospective cohort study looked at neonatal intensive care unit patients with PICC placement between February 2003 and June 2010 at a single medical center in the United States. Results showed that 14/216 patients (6.5%) had sepsis within 5 days of PICC removal. PICC removal because of adverse events was significantly associated with sepsis ( P = .017). Antibiotic use before PICC removal did not have a significant impact on sepsis. The conclusions of the study are that removal of PICCs because of adverse events is significantly associated with late-onset neonatal sepsis and that antibiotic use at the time of PICC removal is not associated with a decline in sepsis rate.